The benefits of guided imagery on athletic performance: a mixed-methods approach - Volgemute, Katrina; Vazne, Zermena; Malinauskas, Romualdas (Frontiers in Psychology, 2025)
IntroductionImagery as a psychological skill in sports occupies an essential place in the psychological preparation of athletes and is one of the key factors in realizing an athlete’s potential in competitive sports. It’s role in athlete performance, as well as the differences in its use across various sports and demographic groups, has been a compelling topic in both sports’ science and psychology. This topic has remained relevant in recent years.AimThis quantitative survey-based and experimental design study aims to first, to determine whether differences in imagery ability profiles, identified through cluster analysis, can characterize differences among athletes with varying levels of athletic achievement. A secondary aim of the study is to evaluate the effect of a guided imagery intervention on imagery abilities and athletic performance.MethodsA total of 500 athletes from different sports, aged M = 21.01 (SD = 2.82), both male and female, completed the Sport Imagery Ability Questionnaire (SIAQ) and provided information regarding their demographics and athletic achievements. In the experimental part of the study, nine alpine skiers were selected to participate in a six-month guided imagery intervention alongside their regular trainings on the ski track to assess the intervention’s impact on performance.ResultsThe results of K-means cluster analysis on athletic achievements of athletes showed a four-cluster solution that hat emphasized distinctions between the groups and reduced variation within each group. A Multiple Analysis of Covariance revealed that the four cluster groups differ in their imagery abilities. Pre- and post-intervention assessments for the nine alpine skiers were conducted using SIAQ and control training sessions, revealing significant increase in both imagery ability scores and performance indicators (p < 0.05).ConclusionThe research results support recent findings that athletes with higher athletic achievement tend to have stronger imagery abilities. The significant differences observed between the clusters based on athletic achievement levels were confirmed. By using imagery profiling of athletes with an analytical method, this study provides valuable insights into the role of imagery in athletic success, suggesting that tailored imagery training could enhance performance across different levels of athletic achievement.